Analysis of the distances covered and technical actions performed by professional tennis players during official matches - Costa Pereira, T. J.; Nakamura, Y.; Tardelli de Jesus, M.; Roveri Vieira, C. L.; Misuta, M. S.; Leite de Barros, R. M.; Arruda Moura, F. (Journal of Sports Sciences, 2017)
The purpose of this study was to analyse the physical and technical performances of professional tennis players during official matches. The trajectories of eight players were obtained during matches, using an automatic tracking method. The distances covered and technical performances were analysed for the first and second sets. The athletes covered (mean ± standard deviation) a total of 1702.4 ± 448.2 m in the first set, 1457.6 ± 678.1 m in the second set and 3160.0 ± 880.1 in the entire match. No differences were found between the sets for the physical variables (lateral and forward displacements, distance covered per rally, per game and per set, and the percentage of time spent in each range of velocity). However, the distances covered by the athletes during the rallies in which they were serving (median = 5.2; interquartile range (IQR) = 6.7 m) were statistically smaller than when they were returning (median = 6.2; IQR = 7.7 m). Forehand ground stroke proficiency decreased from the first (mean ± standard deviation: 75.2 ± 4.11%) to the second set (mean ± standard deviation = 65.5 ± 14.3%). In conclusion, tennis players did not present reduced physical performance from the first to the second set.